Electronic structure of nobel-graphene based superlattices - Garzón Armendáriz, Doménica Nicole (2021)
Graphene has remarkable electronic and structural properties, and it stands out as exceptional material with potential applications in many emerging areas. However, it has limited nanoelectronic applications because it lacks a bandgap at the Fermi level, which defines the concept for semiconductor materials and is essential for controlling the conductivity in the material. Structural defects may change the lack of bandgap in graphene. Nevertheless, because experiments can be time-consuming and expensive, understanding the relationship between defects and structure-related properties is limited. Therefore, it is crucial to investigate the structure-related properties, including defects using DFT simulations and mathematical models. Here it is investigated the atomic and electronic structure, formation energies of graphene-based patterned structures with two types of grain boundary loops, Stone-Wales defects (SWD) and Flower-like defects (FLD). It is investigated the structures through scanning tunneling microscopy, a perturbative mathematical model, and ab initio density-functional theory within the meta-GGA approximation calculations. The analysis shows a bandgap opening in defective graphene superlattice induced by the defects when arranged at certain distances. Then, tight-binding calculations derive a rule that predicts in which cases there may be a gap, and it is compared with DFT results.